2019
DOI: 10.1016/j.cub.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of FLOWERING LOCUS T Modulates Heat-Dependent Source-Sink Development in Potato

Abstract: Highlights d Tuberization is developmentally and temperature dependent regulated via SP6A d SP6A expression is repressed under heat by a small RNA d Abolishing miRNA activity facilitates tuberization, even under strict heat conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 63 publications
2
45
0
4
Order By: Relevance
“…AcFT1 promotes bulb formation, while AcFT4 inhibits bulb production in onions (Lee et al, 2013). Tuberization is regulated by the FT homolog StSP6A through modulation of source-sink in potatoes (Abelenda et al, 2019;Lehretz et al, 2019). Our transgenic plants were thinner than WT, which was caused by overexpression of PbFT.…”
Section: Expression and Function Of Pbftmentioning
confidence: 81%
“…AcFT1 promotes bulb formation, while AcFT4 inhibits bulb production in onions (Lee et al, 2013). Tuberization is regulated by the FT homolog StSP6A through modulation of source-sink in potatoes (Abelenda et al, 2019;Lehretz et al, 2019). Our transgenic plants were thinner than WT, which was caused by overexpression of PbFT.…”
Section: Expression and Function Of Pbftmentioning
confidence: 81%
“…Figure 5) and therefore potentially constitute additional TAC targets. Of these, StMADS17 was previously described to be strongly upregulated in stolons (Gao et al, 2018) and shown to upregulated in the strongly induced to tuberise transgenic SES lines described by Lehretz et al (2019). StMADS17 has homology to SEPALLATA 4 (SEP 4) from Arabidopsis, with a reported role in the regulation of floral meristem development (Ditta et al, 2004).…”
Section: Impact Of Stcen On Stsp6a Gene Expressionmentioning
confidence: 99%
“…Moreover, excessive temperatures have a detrimental effect on photosynthetic performance including severe inhibition of CO 2 fixation and chlorophyll loss in sensitive species (Reynolds et al, 1990). Recent work has demonstrated the mechanisms by which tuberization signaling and initiation is impaired at elevated temperature (Lehretz et al, 2019;Morris et al, 2019). However, there is wide variation for heat stress tolerance across potato germplasm that could be exploited to ensure the sustainability of yield in warmer climates (Levy and Veilleux, 2007;Trapero-Mozos et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%